Acute abdomen due to bilateral ovarian metastases from primary cervical squamous cell carcinoma: A case report - (:unkn) unknown (My University, 2004)
Background: Metastasis from early stage squamous cell carcinoma of the cervix to the ovary is a rare occasion. We present a case of early stage cervical squamous cell carcinoma with bilateral ovarian gross metastases. Case: A 43 year old female with bilateral adnexial mass and in situ cervical carcinoma underwent laparotomy for acute abdomen. Pathological report demonstrated endocervical occult squamous cell carcinoma. The actual stage of the malignancy was IVA because of bilateral ovarian metastasis and positive abdominal cytology due to spontaneous rupture of the ovarian lesions. Conclusion: In this report, importance of preoperative complete evaluation of a patient with known cervical carcinoma is emphasized.
Keywords: Bilateral; Cervix; Ovarian metastasis; Squamous cell carcinoma